How the Activation of the Organizational Change Could Be Affected by the Transformational Leadership? An Applied Study from Bahrain - Samman, Adel Al; Deeb, Horiya Al; Dossary, Wafeea Al; Ahmed, Ahmed Al (International Journal of Social and Administrative Sciences, 2019)
The aim of this study is to analyze the effect of the transformational leadership on the activation of the organizational change process. Formulation of the research topic was based on previous theoretical models that guided researchers to understand the concept of organizational change activation and how to effect it. Outcomes of the research is based on the analysis of the survey that was given out to a representative sample in the ministry of sixty employees. The paper used SPSS statistical analysis software to perform the statistically tests on the data gathered from the sample. Findings revealed that there is a significant relationship between transformational leadership with its dimensions of inspiring encouragement, intellectual stimulation and individual consideration, and activating the organizational change process in one of the Bahraini ministries. Findings also revealed that there is no significant relationship between transformational leadership (inspiring encouragement, intellectual stimulation and individual consideration), and organizational change in the Ministry of Labor and Social Development in Bahrain that could be attributed to demographic variables such as gender, age, qualification, or years of experience and position.